Auditory nerve phase-locked response recorded from normal hearing adults using electrocochleography. - Almohammad, Hana A.; Chertoff, Mark E.; Ferraro, John A.; Diaz, Francisco J. (International Journal of Audiology, 2023)
The auditory nerve overlapped waveform response (ANOW), a new measure that can be recorded non-invasively from humans, holds promise for providing more accurate assessment of low frequency hearing thresholds than currently used objective measures. This research aims to investigate the robustness and the nature of the ANOW response in humans. Repeated within-session recordings of the ANOW response using low-frequency Tone Bursts (TBs) were obtained at multiple stimulus levels. ANOW's absolute amplitude and phase locking value (PLV) measures were analysed to obtain normative data and to test the reliability of the ANOW response. Thirteen normal hearing adults within the age range of 25 to 40 years. ANOW response was obtained to both 250 Hz and 500 Hz TBs and was traced down to 30–40 dB nHL. ANOW response showed significantly higher amplitude and stronger phase locking using 250 Hz TB compared to 500 Hz TB. High degree of test retest reliability of the ANOW response was found using 250 Hz TB at presentation levels higher than 40 dB nHL. ANOW response is recordable noninvasively using low-frequency TBs and shows higher robustness as the stimulus frequency decreases.